2k-4(2k-3)=2(1-4k)

Simple and best practice solution for 2k-4(2k-3)=2(1-4k) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2k-4(2k-3)=2(1-4k) equation:



2k-4(2k-3)=2(1-4k)
We move all terms to the left:
2k-4(2k-3)-(2(1-4k))=0
We add all the numbers together, and all the variables
2k-4(2k-3)-(2(-4k+1))=0
We multiply parentheses
2k-8k-(2(-4k+1))+12=0
We calculate terms in parentheses: -(2(-4k+1)), so:
2(-4k+1)
We multiply parentheses
-8k+2
Back to the equation:
-(-8k+2)
We add all the numbers together, and all the variables
-6k-(-8k+2)+12=0
We get rid of parentheses
-6k+8k-2+12=0
We add all the numbers together, and all the variables
2k+10=0
We move all terms containing k to the left, all other terms to the right
2k=-10
k=-10/2
k=-5

See similar equations:

| X³-2x=21 | | g=1+4/5 | | 30=-6(n-2)-3n | | 7=g+26/5 | | 7-3x+8x=22 | | s/7+82=90 | | 7w+7=5(2w-3)+1 | | -7(x-1)=7(5-5x) | | 2+6r=50 | | y+7/7=3 | | -7v+2(v-6)=13 | | b+3/4=-2 | | 5(2x+8)−5x=5(8x+6) | | 4(5-x)=36 | | 6x-1=7x-7 | | 1/2k+5/6=1 | | -12+6x=2(x-8) | | 6=-2(r+3) | | Y=18+3x^2 | | w-19/6=10 | | 4(v-2)=6v-2 | | 6k-17=55 | | |x+9|=8 | | x^2+4x-36.75=0 | | 5x-5=14x+14 | | w-82/4=3 | | s/9+91=97 | | -4(m+4)=-8 | | 245243657x=456789 | | 300=(x+15)(10+x) | | 4^2x=32^0.5 | | n-1=5+3n |

Equations solver categories